Pod Characteristics of Cocoa (Theobroma cacao L.) Related to Cocoa Pod Borer Resistance (Conopomorpha cramerella Snell.) - Agung Wahyu Soesilo; Surip Mawardi; Witjaksono ,; Woerjono Mangoendidjojo (Indonesian Coffee and Cocoa Research Institute, 2015)
AbstractThe characteristics of pod related to cocoa pod borer resistance (CPB, Conopomorpha cramerella Snell.) had been identified in a series study. This research has objective to evaluate performance of the characteristics using more diverse of genetic background to select criteria for selection. Genetic materials for this study were 25 cocoa clones which be planted in Central Sulawesi for resistant evaluation. Field evaluation of the resistance were assessed using the variable of the percentage of unextractable bean, number of entry and exit hole larvae by which the clones were grouped into 5 groups of resistance. A laboratory works were carried out to assess pod characteristics based on the number of trichome, granule of tannin and thickness the lignified-tissue of sclerotic layer using micro-technique method at the different level of pod maturity (3.0; 3.5; 4.0 months). Correlation between groups of those variables was analyzed using Canonical Correlation. The analysis performed a positive association between the thickness of sclerotic layer at the secondary furrow with the number of entry holes and the number of entry holes through sclerotic layer. The thickness performed a higher value of the coefficient in association with the variables of canonical for pod characteristics (0.59; 0.55; 0.43) and the variables of canonical for CPB resistance (0.54; 0.51; 0.39) that would presenting the characteristics of pod related to CPB resistance. Lignification at sclerotic layer was considered as genotypic expressions due to the thickness at the secondary furrow at 3.0, 3.5 and 4.0 months of pod maturity performed high value of broad-sense heritability i.e. 0.75, 0.89 and 0.92 respectively. A qualitative assessment of the lignification clearly differentiate the resistant clones (ARDACIAR 10) with the susceptible clones (ICCRI 04, KW 516 and KW 564).Key words : cocoa pod borer, Theobroma cacao L., pod characteristics, resistance